Low prevalence of cardiac abnormalities in competitive athletes at return-to-play after COVID-19. Issue 1 (January 2023) - Maestrini, Viviana; Penza, Marco; Filomena, Domenico; Birtolo, Lucia Ilaria; Monosilio, Sara; Lemme, Erika; Squeo, Maria Rosaria; Mango, Ruggiero; Di Gioia, Giuseppe; Serdoz, Andrea; Fiore, Roberto; Fedele, Francesco; et al.
Abstract: Objective: to evaluate the prevalence of cardiac involvement after COVID-19 in competitive athletes at return-to-play (RTP) evaluation, following the recommended Italian protocol including cardiopulmonary exercise test (CPET) and 24-Hour Holter monitoring. Design and methods: this is a single centre observational, cross-sectional study. Since October 2020, all competitive athletes (age ≥ 14 years) evaluated in our Institute after COVID-19, prior RTP were enrolled. The protocol dictated by the Italian governing bodies included: 12‑lead ECG, blood test, CPET, 24-h ECG monitoring, spirometry. Cardiovascular Magnetic Resonance (CMR) was performed based on clinical indication. Results: 219 consecutive athletes were examined (59% male), age 23 years (IQR 19–27), 21% asymptomatic, 77% mildly symptomatic, 2% with previous pneumonia. The evaluation was performed after a median of 10 (6–17) days from negative SARS-CoV-2 swab. All athletes showed a good exercise capacity at CPET without cardiovascular and respiratory limitations. Uncommon premature ventricular contractions (PVCs) were found in 9.5% ( n = 21) at CPET/Holter ECG monitoring. Two athletes (0.9%) were diagnosed with acute myocarditis (by CMR) and another one with new pericardial effusion. All the three athletes were temporally restricted from sport participation. Conclusions: Myocarditis in competitive athletes screened after COVID-19 resolution was detected in a low minority of the cases (0.9%). However, a non-negligible prevalence of uncommon PVCs (9%) was observed, either at CPET and/or Holter ECG monitoring, including all athletes with COVID-19 related cardiovascular abnormalities.